Bibliometric analysis of research trends in digital transformation and mental health from 2014 to 2024 - Daniela-Elena Lițan (Discover Psychology, 2026)
Abstract Digital transformation has significantly reshaped modern society, with important implications for mental health. This study provides a comprehensive overview of the evolution, main contributors, and thematic development of research on digital transformation and its psychological effects. A bibliometric analysis was conducted on studies indexed in the Web of Science Core Collection, Scopus, and PubMed databases, covering the period January 1, 2014 to June 20, 2024. A total of 2287 publications were initially identified, of which 1606 were included in the analysis. The study employed the Biblioshiny application within the Bibliometrix package in RStudio. The bibliometric approach included performance analysis (scientific production, author affiliations, most cited journals, and collaboration networks) and thematic analysis (keyword frequency, research trends over time, co-occurrence networks, longitudinal thematic evolution, and thematic maps). The analysis highlights a substantial increase in research output over the studied period and identifies key contributors and geographical patterns in the field. It reveals important gaps in the literature, particularly regarding the relationship between emerging digitalization components (e.g., remote work, Internet of Things (IoT), virtual reality, blockchain) and mental health. In addition, the findings indicate the rapid emergence of new research directions driven by technological advances, especially in the area of artificial intelligence (AI) and digital environments. This study provides a baseline overview of the field prior to the accelerated expansion of AI-driven research observed after mid-2024. The findings have important implications for mental health research prioritization, clinical awareness, and the development of evidence-based interventions addressing the psychological impact of emerging digital technologies.